UPAYA PENINGKATAN LITERASI BAHASA INGGRIS BAGI ANAK BINAAN PEMASYARAKATAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS II BENGKULU - Sutisyana, Ari; Nopiyanto, Yahya Eko; Maisarah, Ira; Alihsan, Muhammad Iqbal; Nabillah, Muhammad Egi; Suheri, Heppy (Jurnal Abdi Insani, 2025)
The Class II Bengkulu Juvenile Correctional Facility is the only rehabilitation center in Bengkulu Province that provides guidance and development for children and adolescents who have committed criminal offenses. The institution focuses on character building and equipping its residents with skills that can be utilized after their release. Therefore, this community service activity aims to develop English literacy among the children at this facility. As an international language, English literacy is considered essential for these children, as it provides them with the opportunity to acquire foreign language skills—specifically English—which they may have missed or been unable to complete during their formal education. Consequently, the children are expected to gain foreign language competence and the ability to communicate in English. Moreover, English proficiency can open up future job opportunities once they have completed their rehabilitation period. The implementation of this community service activity involved several strategies, including structured classes, interactive learning, and the introduction of digital literacy. The program was attended by 20 resident children. The learning materials provided were still at a very basic level, such as the English alphabet, self-introduction, and identification of everyday objects and daily activities. Overall, this community service activity showed significant results, as indicated by improvements in participants’ English competence based on post-test scores. Thus, it can be concluded that the activity has made a positive contribution and provided tangible benefits for the children at the Class II Bengkulu Juvenile Correctional Facility.